A Flow Cytometry–Based Assay to Measure C3b Deposition on Protozoan Parasites Such as Toxoplasma gondii. Issue 11 (14th November 2022) - Sikorski, Patricia M.; Grigg, Michael E.
Abstract: Flow cytometry is a powerful tool that can be used to study protozoan parasite interactions with the complement system. We developed a flow cytometric assay to measure the deposition of complement activation product C3b and to assess resistance to complement‐mediated lysis. This assay involves exposing cultured parasites to human serum (the source of human complement) and staining parasites with antibodies against complement proteins to detect and quantify complement components on the parasite surface by flow cytometry. The assay can be used to compare complement activation across a variety of different species of protozoan parasites. As a proof of concept, we describe protocols to study C3 deposition on the single‐cell protist Toxoplasma gondii . This parasite actively regulates C3 deposition and proteolytic inactivation to eliminate the formation of lytic pores targeted to the parasite surface coat, which is the end‐product of the complement cascade. The antibodies used in this assay recognize both active and inactive forms of C3 deposited on parasite surfaces. Hence, the assay facilitates the identification and characterization of parasite resistance factors that regulate complement deposition and catabolic inactivation. © Published 2022. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol 1 : Culturing human foreskin fibroblasts and Toxoplasma gondii strains Basic Protocol 2 : In vitro complement activation assay Support Protocol : Screening of normal human serum Basic Protocol 3 : Flow cytometric analysis of C3b deposition